A study of conditions in the upper atmosphere and their deduction from radio measurements - Gledhill, J A,Szendrei, M E (Rhodes University, Faculty of Science, Department of Physics, 1948)
Summary: In part 1 (a), after a brief historical outline of methods of ionospheric investigation and their development, the construction in this laboratory of manually operated equipment for sounding the ionosphere is described. Photographic records of good definition were taken at regular intervals over a period of four months during the summer of 1945-6. These were fully sealed for critical frequencies, true heights and thicknesses of all the layers present, and mean monthly values of these quantities for each hour are tabulated. An extensive correlation with magnetic data from Hermanus indicated good correlation between magnetic activity and disturbed ionospheric conditions. On these grounds some disturbed days were rejected, and others were eliminated on ionospheric grounds. Smoothed mean values are tabulated and graphs drawn. These are presented in concise form on "electron density maps", which are graphs showing lines of constant electron density plotted as functions of time and height. In part 1 (b), a new theory of layer-formation is developed, in which the temperature is assumed to vary linearly with height. The equations are compared at each step with those obtained by Chapman in his theory of layer-formation in an isothermal atmosphere. The equations for the maximum of electron density and its height are also given. The effect of the parameters on the shape of the layer is shown in graphical form. The equations are somewhat complex in form, but an ingenious graphical method has been devised suitable for the application of the theory to results given in the form of those in section 1 (a). From this application values are obtained for the temperature gradient, the temperature at 200 km. and its variation over the middle part of the day. The results obtained are in accordance with previous estimates, and offer numerical confirmation of the theory that the atmosphere expands bodily upwards during the middle part of a summer day.
Keywords: Uncatalogued